Stress Induces p38 MAPK-Mediated Phosphorylation and Inhibition of Drosha-Dependent Cell Survival - Yang, Qian; Li, Wenming; She, Hua; Dou, Juan; Duong, Duc M.; Du, Yuhong; Yang, Shao-Hua; Seyfried, Nicholas T.; Fu, Haian; Gao, Guodong; Mao, Zixu (Molecular cell, 2015)
MicroRNAs (miRNAs) regulate the translational potential of their mRNA targets and control many cellular processes. The key step in canonical miRNA biogenesis is the cleavage of the primary transcripts by the nuclear RNase III enzyme Drosha. Emerging evidence suggests that the miRNA biogenic cascade is tightly controlled. However, little is known whether Drosha is regulated. Here, we show that Drosha is targeted by stress. Under stress, p38 MAPK directly phosphorylates Drosha at its N terminus. This reduces its interaction with DiGeorge syndrome critical region gene 8 and promotes its nuclear export and degradation by calpain. This regulatory mechanism mediates stress-induced inhibition of Drosha function. Reduction of Drosha sensitizes cells to stress and increases death. In contrast, increase in Drosha attenuates stress-induced death. These findings reveal a critical regulatory mechanism by which stress engages p38 MAPK pathway to destabilize Drosha and inhibit Drosha-mediated cellular survival. [Display omitted] •p38 directly phosphorylates Drosha and reduces its interaction with DGCR8•Phosphorylation subjects Drosha to nuclear export and degradation by calpain•Drosha activity is required for cell survival•Stress induces death in part by inhibiting Drosha-mediated survival Drosha can be regulated under stress conditions. Yang et al. find that p38 MAPK directly phosphorylates Drosha, which reduces its interaction with DGCR8, promotes its nuclear export and degradation by calpain, and increases cell death under stress.